Community Satisfaction level AnalysisIn land Certificate Making Services In Bengkulu City land Office - Cinthya Jennifer Rumondang Nainggolan; Evi Lorita; Harius Eko Saputra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study aims to determine the level of community satisfaction in the service of making land certificates at Bengkulu City Land Office. This research method uses quantitative research with descriptive survey methods and data analysis techniques using community satisfaction index analysis techniques based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. In collecting data, the researcher used questionnaires, observations and documentation. The population and sample in this study were registered service users, as many as 74 respondents. The sampling technique used is saturated sampling. Based on the results of the study, it shows that community satisfaction in the service of making land certificates at Bengkulu City Land Office has been going very well where the results obtained from (1) Requirements with an interval value of 4.41 categories are very satisfied; (2) Systems, Mechanisms and Procedures with an interval value of 4.44 in the very satisfied category; (3) completion time with an interval value of 3.79 satisfied category; (4) Costs/Tariffs with an interval value of 4.52 very satisfied category; (5) Product Specification Type of Service with an interval value of 4.36 very satisfied category; (6) Implementing Competence with an interval value of 4.41 in the very satisfied category. (7) Implementing behavior with an interval value of 4.46 in the very satisfied category; (8) Handling of Complaints, Suggestions and Feedbacks with an interval value of 4.24 in the very satisfied category; (9) Facilities and infrastructure with an interval value of 4.36 in the very satisfied category. The weighted average score is 85.76, with a service value of "A" and a service unit performance of "Very Satisfied".